MENGUKUR KEPUASAN COSTUMER TERHADAP KUALITAS LAYANAN SISTEM INFORMASI PERPUSTAKAAN STMIK AKBA MENGGUNAKAN METODE KANO - First Wanita; Ashari; Nurpaida (Fakultas Teknik Universitas Lambung Mangkurat, 2016)
Library is one of the critical success factors for students in conducting studies hence the demand for services for the library system are also higher, with the hope of any information or collections are sought can be accessed quickly, accurately, easily with high quality. Therefore, this study was conducted to measure how satisfied users for service quality library system that exists today in STMIK CMR, a measure of the library system is done by utilizing the method of the canoe. In this method the quality factor is divided into five categories, namely must be, one-dimensional, attractive, indifference and reverse that has characteristics and different levels of influence on consumers. This study used a questionnaire as a research instrument. From the results of taking the measurements filling the questionnaire of 3 respondents system was declared fit for use for measuring kualitan system service information library of seeing the results presentation on aspects of testing on the level of conformity of the respondents received good response with a value ≥ 75% and this system can also be known information about requirements desired by the user so that later can provide a service that corresponds to that desired by the user.